2006
DOI: 10.1109/jlt.2006.876898
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-likelihood sequence detection with closed-form metrics in OOK optical systems impaired by GVD and PMD

Abstract: Abstract-This paper thoroughly investigates the maximumlikelihood sequence detection (MLSD) receiver for the optical ON-OFF keying (OOK) channel in the presence of both polarization mode dispersion and group velocity dispersion (GVD). A reliable method is provided for computing the relevant performance for any possible value of the system parameters, with no constraint on the sampling rate. With one sample per bit time, a practically exact expression of the statistics of the received samples is found, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Maximum likelihood sequence detection is the proven to be the most effective technique for mitigating optical channel impairments such as chromatic dispersion and polarization mode dispersion (Foggi et al, 2006). In order to successfully apply this technique, it is mandatory to estimate some key channel parameters needed by the Viterbi processor.…”
Section: Metrics Generation and Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Maximum likelihood sequence detection is the proven to be the most effective technique for mitigating optical channel impairments such as chromatic dispersion and polarization mode dispersion (Foggi et al, 2006). In order to successfully apply this technique, it is mandatory to estimate some key channel parameters needed by the Viterbi processor.…”
Section: Metrics Generation and Updatementioning
confidence: 99%
“…It is clear that in (3.2) 0 N and  need to be estimated. More information about parametric estimation is given in (Agazzi et al, 2005;Foggi et al, 2006).…”
Section: Metrics Generation and Updatementioning
confidence: 99%
“…The excellent agreement deserves no further comment. It can be observed that, provided the value of is sufficiently large, the performance of the b2b 12 As shown in [38], the ratio E =N represents the number of detected photons per bit at the input of the optical amplifier and is related to the optical signal-to-noise ratio (OSNR) by E =N = 22 OSNR 2 WT, with W being the reference measurement bandwidth usually taken equal to 12.5 GHz (0.1 nm). case, also shown for comparison, can be attained.…”
Section: A Performance In the Absence Of Phase Noisementioning
confidence: 99%
“…Since a square-law detector is used at the receive end, postdetection noise statistics change [1], [10], [11], and can no longer be considered Gaussian. A suitable closed-form expression of the branch metrics of the Viterbi algorithm (VA) implementing the MLSD strategy is provided in [7] and [8]. However, some parameters of the distribution of the received samples depend not only on the transmitted pulse shape, filter types, and bandwidths, but also on the channel impairments and on the noise power spectral density (PSD) [8].…”
Section: Introductionmentioning
confidence: 99%
“…A suitable closed-form expression of the branch metrics of the Viterbi algorithm (VA) implementing the MLSD strategy is provided in [7] and [8]. However, some parameters of the distribution of the received samples depend not only on the transmitted pulse shape, filter types, and bandwidths, but also on the channel impairments and on the noise power spectral density (PSD) [8]. Due to the square-law nature of a photodiode, the estimation of the required channel parameters is not straightforward.…”
Section: Introductionmentioning
confidence: 99%